The Addition Effect of Rhodium (III) Sulfate and Clove Oil on the Combustion Characteristics of Castor Oil Droplet - Purnami, Purnami; Wardana, I.N. G.; Hamidi, Nurkholis; Sasongko, Mega Nur; Darmadi, Djarot B. (International Journal of Integrated Engineering, 2019)
The petroleum fuels reserves from fossils are getting smaller, even though petroleum consumption is increasing. Given the increasingly limited amount of fuel derived from fossils, it is necessary to do research to look for alternative fuels. Castor oil is one of the alternative plant oils that can replace petroleum fuels. Castor oil is a non-food crop which numbers is relatively many in Indonesia. But castor oil has limitations on its combustion property, so combustion of castor oil cannot produce energy that is as large as petroleum combustion. It is necessary to add catalysts to improve the combustion properties of castor oil. In this study. the addition of Rhodium (III) Sulphate and clove oil was performed to improve the castor oil combustion properties. Addition of catalyst is intended to reduce dissociation energy requirements, so that the combustion reaction is faster. The addition of Rhodium (III) sulfate and clove oil catalysts is 100 ppm, 200 ppm, 300 ppm and 400 ppm. The results showed that the addition of catalysts affected the castor oil combustion characteristics. The more addition of Rhodium (III) Sulfate catalysts and clove oil can reduce the combustion temperature value, ignition delay, burning rate, and fire dimensions. Rhodium (III) Sulphate is more effective in influencing combustion characteristics than clove oil.